2012
DOI: 10.1242/dev.067314
|View full text |Cite
|
Sign up to set email alerts
|

p57KIP2 regulates radial glia and intermediate precursor cell cycle dynamics and lower layer neurogenesis in developing cerebral cortex

Abstract: SUMMARYDuring cerebral cortex development, precise control of precursor cell cycle length and cell cycle exit is required for balanced precursor pool expansion and layer-specific neurogenesis. Here, we defined the roles of cyclin-dependent kinase inhibitor (CKI) p57 KIP2 , an important regulator of G1 phase, using deletion mutant mice. Mutant mice displayed macroencephaly associated with cortical hyperplasia during late embryogenesis and postnatal development. Embryonically, proliferation of radial glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 58 publications
(99 reference statements)
4
86
1
1
Order By: Relevance
“…2B), indicating that overexpression of Hbp1 caused an attenuation of cell proliferation or premature cell cycle exit. We then carried out a calculation of cell cycle kinetics by BrdU/EdU double-labeling protocol [modified from a previously described IdU/BrdU double-labeling method (Martynoga et al, 2005;Mairet-Coello et al, 2012)] and estimated the cell cycle length. Cells transfected with pEF-Hbp1 showed a slightly longer cell cycle length compared with control ( Fig.…”
Section: Overexpression Of Hbp1 Suppresses Cell Proliferation But Inmentioning
confidence: 99%
See 1 more Smart Citation
“…2B), indicating that overexpression of Hbp1 caused an attenuation of cell proliferation or premature cell cycle exit. We then carried out a calculation of cell cycle kinetics by BrdU/EdU double-labeling protocol [modified from a previously described IdU/BrdU double-labeling method (Martynoga et al, 2005;Mairet-Coello et al, 2012)] and estimated the cell cycle length. Cells transfected with pEF-Hbp1 showed a slightly longer cell cycle length compared with control ( Fig.…”
Section: Overexpression Of Hbp1 Suppresses Cell Proliferation But Inmentioning
confidence: 99%
“…To estimate the cell cycle length, we conducted a dual-pulse-labeling of DNA synthesis using 5-bromo-2′-deoxyuridine (BrdU; Sigma-Aldrich) and 5-ethynyl-2′-deoxyuridine (EdU; Molecular Probes), referring to the previous methods (Martynoga et al, 2005;Mairet-Coello et al, 2012). Previous reports used EdU first, followed by BrdU, but here we administered BrdU first, followed by EdU.…”
Section: Analysis Of Cell Cycle Lengthmentioning
confidence: 99%
“…Kip2 or p27 Kip1 increases NPC proliferation, expanding the pool of NPCs and resulting in a larger brain (Caviness et al, 2003;Goto et al, 2004;Mairet-Coello et al, 2012;Nguyen et al, 2006a;Tury et al, 2011). By contrast, overexpression of either CKI induces premature NPC terminal mitosis and differentiation, reducing the size of the NPC pool and consequently the size of the brain Tarui et al, 2005;Tury et al, 2011;Tury et al, 2012).…”
Section: Deletion Of Either P57mentioning
confidence: 99%
“…Kip1 is more highly expressed in IPCs and regulates the terminal mitosis and differentiation of neurons primarily destined for cortical layers II-V (Goto et al, 2004;Mairet-Coello et al, 2012;Mitsuhashi et al, 2001;Tarui et al, 2005). Since gain-of-function of either p57…”
Section: Do Changes In Mcl1 Expression Affect P27mentioning
confidence: 99%
“…15,16 It is well known that neuronal progenitor cell fate can be affected by cell cycle regulators including cyclins, [17][18][19] Cdks 20 and their inhibitors. [21][22][23][24] In the developing central nervous system (CNS), mRNA of cyclin D2 shows a unique localization, to the surface of the neural tube, not seen for other cyclins. 25,26 Because of this unique localization pattern, cyclin D2 was initially thought to be expressed in postmitotic neurons 25,26 but recent work identified that the mRNA and protein localized at the tip of the AP (i.e., endfoot).…”
Section: Cyclin D2 and Brain Evolutionmentioning
confidence: 99%